Peran Pendamping dalam Meningkatkan Kemandirian pada Anak di Yayasan Sayap Ibu Cabang D.I. Yogyakarta - Siska Hermalida; Pajar Hatma Indra Jaya (CV. Ulil Albab Corp, 2023)
A companion (social worker) is someone whose job is to provide services, guidance and guidance so that children not only increase their knowledge but also their independence. This research aims to determine (a) the role of companions in increasing independence in children at the Sayap Ibu Foundation, D.I. Branch. Yogyakarta; and (b) supporting and inhibiting factors in increasing independence in children at the Sayap Ibu Foundation, D.I. Branch. Yogyakarta. The method used in this research uses a qualitative approach and descriptive research type. The subjects of this research consisted of companions (social workers). Data collection techniques consisted of observation, interviews and documentation. Data analysis techniques consist of data reduction, data collection, data presentation, and drawing conclusions. The research results show that the role of companions in increasing children's independence can be realized well, such as; implementing writing activities, calistung, making creative batik, splattered batik, painting and sewing. From making creative batik and cipra batik, the products can be marketed. The children also seemed enthusiastic about carrying out various programmed activities themselves without involving other people, so that the role of companions was one of the influences.